2005
DOI: 10.1111/j.1572-0241.2005.41336.x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Educational Strategy to Enhance Internal Medicine Residents' Familial Colorectal Cancer Knowledge and Risk Assessment Skills

Abstract: A mixed educational program that incorporates both a DL and ICBS is more effective that the DL alone for increasing knowledge about familial CRC risk but may have limited influence on clinical risk assessment skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…These findings contribute to studies demonstrating the value of educational interventions in hereditary cancer (Blazer et al 2004;Carroll et al 2009Carroll et al , 2011Houwink et al 2013Houwink et al , 2014aSchroy et al 2005;Watson et al 2001). Watson showed improved referral decisions for patients with a FH of breast/ovarian cancer, using mailed information including a laminated summary card with simple referral guidelines, a booklet with more detailed information, and two patient leaflets (Watson et al 2001).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…These findings contribute to studies demonstrating the value of educational interventions in hereditary cancer (Blazer et al 2004;Carroll et al 2009Carroll et al , 2011Houwink et al 2013Houwink et al , 2014aSchroy et al 2005;Watson et al 2001). Watson showed improved referral decisions for patients with a FH of breast/ovarian cancer, using mailed information including a laminated summary card with simple referral guidelines, a booklet with more detailed information, and two patient leaflets (Watson et al 2001).…”
Section: Discussionmentioning
confidence: 55%
“…Watson showed improved referral decisions for patients with a FH of breast/ovarian cancer, using mailed information including a laminated summary card with simple referral guidelines, a booklet with more detailed information, and two patient leaflets (Watson et al 2001). Schroy et al (2005) showed that a mixed educational program incorporating both a didactic lecture and interactive case-based seminar increased knowledge about familial CRC risk in internal medicine residents but was ineffective in changing resident behavior such as clinical risk assessment. However, their intervention's impact on knowledge declined over time highlighting the need for practical, available tools (Schroy et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study validated a simpler method of VTE risk grouping that performs well regardless of clinical experience. 20 Future studies are needed to determine whether there is improved resident inter-rater reliability using a point-based risk assessment tool that is embedded into a computerized order entry system with electronic reminder alerts. Finally, in actual clinical settings, the question remains of whether kappa scores correlate with protocol adherence, prophylaxis rates, and VTE reduction when using point-based tools.…”
Section: Discussionmentioning
confidence: 99%
“…Since previous research demonstrates the utility of clinical vignettes to study the effectiveness of guideline application and decision making, we used a series of 21 randomly selected and de-identified clinical vignettes to portray a range of real-world patient admission scenarios. [20][21][22] We identified individuals who had been admitted to the Hershey Medical Center using data from the inpatient electronic health record and applying the following inclusion criteria: age >17 years, and admission to a general medical service from the Emergency Department during a 14-day period in 2008. Since more than 80% of patients admitted to our medical service are admitted through the Emergency Department and residents place all of the admission orders, our goal was to use vignettes that were typical of patients they commonly admit.…”
Section: Construction Of Clinical Vignettesmentioning
confidence: 99%